Christianity a very short introduction - Woodhead, Linda (Very short introductions., 2004)
"Christianity: A Very Short Introduction offers an overview of the world's largest religion. The Author provides information to enable the reader to gain an understanding of Christians and their beliefs" --Provided by publisher.